The Model of Failure for Exploited Brick Buildings in the Conditions of an Unevenly Deformed Base - Kichaeva, Oxana (International Journal of Engineering and Technology, 2018)
The article proposes a model of failure for exploited brick structures and buildings in the conditions of an unevenly deformed base as a function of time. This model includes the corresponding models of the structural element, loads and effects, the base model, the material model, the environmental impact model, and the phenomenological model of damage accumulation. The author has constructed the distribution function of the generalized force influence on brick buildings in the conditions of an unevenly deformed base. Based on the results of experimental studies, the mechanisms of destruction of brickwork in conditions of a single-axial stress state are formulated. A solution has also been proposed that makes it possible to determine the coefficients of the elastic base for a layered base with any number of layers with different deformation characteristics. The laws of the distribution of such brick parameters are obtained: compressive strength, flexural strength, length and height, also the possibility of applying the normal distribution law for the properties of the materials of the exploited structures is shown. In the damage accumulation model, it is suggested that the criterion for the technical state of a brick element is to take a set of numerical parameters of cracks in the material: the width of crack opening, the length and density of cracks. The aggregate of these numerical parameters is a quantitative integral characteristic of the degradation process. The connection of the above parameters with reliability makes it possible to assess the reliability of the element in the crack resistance, depending on the exploiting time. The reliability assessment of an element is formulated as a search for the probability of the non-exceeding of the limiting state by the controlled parameter, after which the probability of non-extinction by the generalized parameter is determined. The proposed model can serve to predict the resource of the Â«building-baseÂ» system at all stages of the life cycle.Â Â